IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MANUSKRIP DI PERGURUAN TINGGI KEAGAMAAN ISLAM (PTKI) - Herman, Herman (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
This article is aimed to describe the implementation of manuscript-based learning model. Manuscript-based learning model is a learning model which instill manuscript values among the students, so that they will respect, love, and cherish the manuscript values as well as able to apply them in real life. The study was conducted in a qualitative approach employing library research method. Data collection was performed by reading various relevant literature associated with the implementation of manuscript-based learning model in Islamic higher education. The study figured out that to implement manuscript-based learning model in Islamic higher education can be performed through the following ways: 1) fostering sense of love, appreciation, and belonging toward the manuscripts, 2) building the character and sense of nationalism through the manuscript, 3) developing texts into manuscript moderation, 4) associating the manuscript with social realities, and 5) reviewing the past to prepare for the better future. The result of study is recommended to the leaders and lecturers of Islamic higher education in order to carry on this learning model responsibly, accountably, and cooperatively with other stakeholder.